Grammatical Errors Made By Students’ on the Technique of Making Idiomatic Translation in the Politic Texts - Siska Widya (English Language Teaching Prima Journal (ELT), 2021)
English is an important role in education or technology since it functions as one of the international languages. The aim is to describe a type of grammatical error and find out the causes of errors in translating vocative text based on the idiomatic translation. The research was conducted at SMP Swasta Al-Maksum. The research design used descriptive quantitative. The population of this research was students consist of 41 students. The technique sampling was purposive sampling, sample is 41 students. The test was teacher-made. The data were acquired by administrating an objective test was a text which consisted of 10 items to test their knowledge in translating the text based on idiomatic translation, each correct translation has scores one and the incorrect translation was scored zero. The findings showed that 71% of samples were able and 29% of samples were unable in translating the text based on idiomatic translation. It means that students were able to translate the text-based on idiomatic translation.